PEMBUATAN ALAT UJI DISTORSI CAHAYA PADA KACA SPION DI PT. ASTRA KOMPONEN INDONESIA - , DWI WAHYU PRASETYO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Mirror is a completeness standard part of vehicle. In the production process of mirror must appropriate Japan International Standard (JIS) and Standar Nasional Indonesia (SNI). One of mirror quality parameter is distortion factor. Distortion of mirror is defect on the mirror which cause the imagination not be like its original. To known value of factor distortion needed distortion testing process. Distortion detection mirror is equipment which used to known distortion value from mirror have been production. In the distortion testing mirror, mirror will stand in front of circle pattern. And then, put a camera in the center circle pattern will take picture in displayed in the mirror. Not all picture is perfect circle which displayed in the mirror. After the pattern be like standard, next process is measure length from center point of circle pattern to the outset circle in every defined poin then calculate it to get distortion value. As a verification standard so maximal distortion value on the flat mirror is 0,2 %. It is 10 % from 2 % maximal distortion value on D01N mirror. From the result of distortion testing on the flat mirror have distortion value 0,18 %. Because of that so this equipment testing can be used.